Spatial Transmission Optimization for Secondary Users in Next-Gen Directional Networks - Zeinab Kteish; Jad Abou Chaaya; Abbass Nasser; Koffi-Clement Yao; Ali Mansour (IEEE Access)
Concurrent transmission of the opportunistic Secondary User (SU) and the licensed Primary User (PU) is a promising approach to increasing secondary network capacity in Cognitive Radio (CR) networks. In future telecommunication generations, PU can be expected to adopt directional transmission. This allows SU to exploit the spatial dimension in addition to the time-frequency dimensions, as in classical CR. However, sensing the beam of the PU and optimizing the transmission parameters of SU become crucial in this scenario to avoid interference between the SU and PU. In this paper, we propose a concurrent transmission strategy, where SU independently and passively senses the position and beamwidth of PU. Once the PU’s beam is detected, SU becomes allowed to direct its transmit power in the unoccupied space, leading to improved spectrum efficiency of the CR network. The proposed strategy aims to optimize the transmission power directed toward the secondary receiver so that the interference coming from the secondary lobes does not exceed an interference threshold. Given the role of transmit power and the number of antenna elements in determining the transmission characteristics of the SU, we formulate the allowed transmission power that respects tolerable interference to the PU. Additionally, we investigate the number of antenna elements at the SU by developing a non-convex optimization problem and proposing a method to address it. Finally, we formulate the capacity of the SU network and compare it to the traditional opportunistic CR approach. Numerical results investigate the functionality of the proposed strategy in relation to the primary network transmission conditions and potential errors in estimating these conditions. Simulation results demonstrate a significant capacity increase compared to conventional CR, where SUs only transmit during channel idle periods.